Pertimbangan Hakim Terhadap Pelaku Tindak Pidana Pembakaran Polsek Candipuro Lampung Selatan (Studi Putusan Nomor: 285/Pid.Sus/2021/PN.KLA) - Retno Wulansari; I Ketut Seregig; Suta Ramadan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
As a state of law, Indonesia applies its own rules in administering the system of government, society, nation and state. The 1945 Constitution is the constitution of the Unitary State of the Republic of Indonesia. In general, the law is marked by the existence of commands and prohibitions that must be obeyed by everyone in it. The need for Law Number 11 of 2008 concerning Information and Electronic Transactions, in other words the Indonesian people are currently very relevant to regulations in the field of electronic transactions. The research method using juridical as a first step in evaluating the formation of norms and rules in Law Number 11 of 2008 concerning Information and Electronic Transactions must be considered to have been completely completed as stipulated in the Act. Law Number 11 of 2008 concerning Information and Electronic Transactions is the first law in the field of information technology and electronic transactions as a product that is very much needed and has become a pioneer in laying the basis for regulations in the field of utilizing information technology and electronic transactions, but in reality, the implementation of Law Number 11 of 2008 concerning Information and Electronic Transactions has encountered problems. Plus, the rapid advancement of technology makes people commit crimes on social media, people are seen as producers and distributors of information. The judge's decision is one of the most important aspects in determining the realization of a judge's decision that contains justice for the parties concerned.